2015
DOI: 10.1093/aob/mcv180
|View full text |Cite
|
Sign up to set email alerts
|

Selenium accumulation by plants

Abstract: The trait of Se hyperaccumulation has evolved several times in separate angiosperm clades. The ability to tolerate large tissue Se concentrations is primarily related to the ability to divert Se away from the accumulation of selenocysteine and selenomethionine, which might be incorporated into non-functional proteins, through the synthesis of less toxic Se metabilites. There is potential to breed or select crops with greater Se concentrations in their edible tissues, which might be used to increase dietary Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
362
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(374 citation statements)
references
References 206 publications
8
362
0
4
Order By: Relevance
“…Activating sulfate transporter is conducive to promoting Se uptake and translocation from roots to shoots in plants [51][52][53][54]. In this study, the data of RNA-Seq revealed that the release of VOCs released by BF06 induced the expression of sulfate transporter genes including SULRT1;1, SULRT1;2, SULTR2;1, SULTR2;2 and SULTR3;5, indicating that BF06 VOCs was likely involved in the regulation of Se uptake in Arabidopsis.…”
Section: Effects Of Bf06 Vocs On Se Accumulation In Plantsmentioning
confidence: 56%
See 2 more Smart Citations
“…Activating sulfate transporter is conducive to promoting Se uptake and translocation from roots to shoots in plants [51][52][53][54]. In this study, the data of RNA-Seq revealed that the release of VOCs released by BF06 induced the expression of sulfate transporter genes including SULRT1;1, SULRT1;2, SULTR2;1, SULTR2;2 and SULTR3;5, indicating that BF06 VOCs was likely involved in the regulation of Se uptake in Arabidopsis.…”
Section: Effects Of Bf06 Vocs On Se Accumulation In Plantsmentioning
confidence: 56%
“…In this study, combined analyses of RNA-Seq and qRT-PCR confirmed that the release of VOCs by BF06 distinctly upregulated the expression of several sulfate transporter genes including SULRT1;1, SULRT1;2, SULTR2;1, SULTR2;2, and SULTR3;5, which are involved in the regulation of Se uptake and translocation [51][52][53][54]. For this purpose, we investigated the effects of microbial VOCs on Se absorption in Arabidopsis plants.…”
Section: Bf06 Vocs Regulates Plant Uptake Of Se By Upregulating Of Sumentioning
confidence: 68%
See 1 more Smart Citation
“…We therefore attach great importance to the QTL located on 3D, which were found to be associated with both root characteristics and grain Se concentration. As plants uptake mineral elements from the soil via the roots, we believe that Qse-3D improves Se concentration by controlling the root morphology and architecture, or Se phytoavailability (White 2016a). Future work should thus aim to determine the candidate genes that might control Se concentrations.…”
Section: Molecular Marker Utilizationmentioning
confidence: 99%
“…Associations between genotypic variation and mineral element concentrationn wheat have been reported (Chao et al 2014, White 2016a, and improving the concentration in minerals is achievable through the utilization of germplasm resources (Lyons et al 2005). We found higher genotypic variation in the synthetic hexaploid lines at low Se conditions, implying that Se concentrations in the tissues are associated with the wheat genotype.…”
Section: Potential Use Of Synthetic Wheatmentioning
confidence: 99%